2017
DOI: 10.4103/sja.sja_237_17
|View full text |Cite
|
Sign up to set email alerts
|

Reducing by 50% the incidence of maternal hypotension during elective caesarean delivery under spinal anesthesia: Effect of prophylactic ondansetron and/or continuous infusion of phenylephrine - a double-blind, randomized, placebo controlled trial

Abstract: Background:Prophylactic administrations of ondansetron or phenylephrine have been reported to provide a protective effect against hypotension in women undergoing cesarean delivery under spinal anesthesia (SA). The main hypothesis is that ondansetron improves the hemodynamic response, especially combined with phenylephrine infusion.Methods:This prospective, double-blind, randomized, placebo-controlled study included 265 healthy pregnant women scheduled for elective cesarean delivery under SA. Women were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 21 publications
(26 reference statements)
2
20
1
Order By: Relevance
“…We included 109 out of 1021 retrieved trials, which included 8561 women (Fig. and see also Supporting Information, Table S1) . Twelve interventions (eleven active treatments and one inactive control) to prevent intra‐operative hypotension were studied, with 30 direct comparisons (see also Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…We included 109 out of 1021 retrieved trials, which included 8561 women (Fig. and see also Supporting Information, Table S1) . Twelve interventions (eleven active treatments and one inactive control) to prevent intra‐operative hypotension were studied, with 30 direct comparisons (see also Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Overall the deceased dose of intrathecal bupivacaine along with longer period of fasting could have resulted in the lack of effect of ondansetron on the blood pressure following the administration of spinal anesthesia. The same groups of investigators recently performed a similar study with larger sample size of 67 patients in ondansetron group and concluded that although ondansetron does not decrease the incidence of maternal hypotension it does reduce the severity of hypotension reducing the number of hypotensive episodes per patient by 50% 20 .…”
Section: Discussionmentioning
confidence: 94%
“…handled the same perspective and reported no difference between the study groups regarding patient demographics. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases, fetal acidosis and bradycardia along with cardiovascular collapse could be encountered. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%